(Effect of Distillation Time and Particle Size on The Yield and Physico-Chemical Properties of White Pepper Oil Waste (Piper nigrum Linn)) - -, Lucyana; -, Sumarsi (Warta Industri Hasil Pertanian, 1993)
A study on the effect of distillation time and physico-chemical properties of while pepper waste had been done.The particle sizes were ground pepper and whole pepper,and the distllation method waswater and steam distillation for 2,4,6,8, and 10 hours.The yield of pepper oil of whole pepper were 1.56, 1.84, 2.77, and 2.97% respectively.For the ground pepper the yield were 2.50, 2.77, 2.81, 2.88, and 3.24%.The main components of the oil were alpha-pinene,beta-pinene,limonene and beta-caryophyllene.The physico-chemical test showed that the oil was suited the requirement of EOA(Essential Oil Assosiation Of America)